Structural differences between the closed and open states of channelrhodopsin‐2 as observed by EPR spectroscopy. Issue 20 (10th September 2013) - Krause, Nils; Engelhard, Christopher; Heberle, Joachim; Schlesinger, Ramona; Bittl, Robert
Abstract : Channelrhodopsin is a cation channel with the unique property of being activated by light. To address structural changes of the open state of the channel, two variants, which contain either 1 or 2 wild‐type cysteines, were derivatised with nitroxide spin label and subjected to electron paramagnetic resonance spectroscopy. Both variants contained the C128T mutation to trap the long‐lived P 3 520 state by illumination. Comparison of spin–spin distances in the dark state and after illumination reflect conformational changes in the conductive P 3 520 state involving helices B and F. Spin distance measurements reveal that channelrhodopsin forms a dimer even in the absence of intermolecular N‐terminal cysteines. Abstract : We find specific dimerization independent of cysteine residues. ChR2 shows a structural change in helix F upon light excitation as in other retinal proteins. We find additional structural changes in either helix B or the dimerization interface.